Managing Interfaith Education for Pluralism: An Educational Strategy to Counter Radicalization in Contemporary Society - Kardina Engelina Siregar; Ahmad Sa'adi; Iwan Siswanto; Saidah Oktariyati (Journal of Educational Management Research, 2026)
Interfaith education and pluralism have increasingly been recognized as strategic approaches to counter radicalism and extremism in contemporary society. This study aims to analyze the role of interfaith education that respects religious diversity in reducing tendencies toward radicalism. Employing a qualitative research approach, the study explores the implementation of structured interfaith education programs and examines their influence on individuals’ perceptions of other religions. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed thematically within the framework of pluralism theory. The findings reveal that well-designed and sustained interfaith education fosters deeper understanding of religious values, promotes attitudes of tolerance and mutual respect, and significantly reduces the inclination to adopt radical ideologies. These programs also contribute to strengthening social cohesion and intercultural dialogue. The study implies that interfaith education plays a crucial role in educational and social management as a preventive and deradicalization strategy, offering a transformative perspective on the role of religion in addressing contemporary social challenges and promoting peaceful coexistence in plural societies.